2022
DOI: 10.12913/22998624/152464
|View full text |Cite
|
Sign up to set email alerts
|

Oil Shale Ash as a Substitutional Green Component in Cement Production

Abstract: The energy crisis is one of the major challenges confronting the cement industry today. Although non-renewable energy sources are becoming scarce, the presence of significant quantities of oil shale indicates its continued use as an energy source in the cement industry. However, significant environmental impacts may occur as a result of the large amount of oil shale ash (OSA). As a result, the researchers are investigating alternative methods for recycling and reusing the OSA in a variety of applications. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…In this context, it is worth mentioning that the grinding stage of cement production takes place more quickly and with less energy consumption when OSA particles smaller than the clinker are added to the process [45]. It has been reported that the concrete's compressive strength decreases with increasing OSA content since it increases the water demand and increases the w/c ratio of the mixes, corroborating other results in the literature [39,41,42].…”
Section: Osa Specific Surface Areasupporting
confidence: 85%
See 1 more Smart Citation
“…In this context, it is worth mentioning that the grinding stage of cement production takes place more quickly and with less energy consumption when OSA particles smaller than the clinker are added to the process [45]. It has been reported that the concrete's compressive strength decreases with increasing OSA content since it increases the water demand and increases the w/c ratio of the mixes, corroborating other results in the literature [39,41,42].…”
Section: Osa Specific Surface Areasupporting
confidence: 85%
“…• Adding OSA to concrete reduces its fluidity and increases its saturation point • The strength and frost resistance of concrete reduces as the OSA content in its composition increases Alsafasfeh et al [45] Compressive strength • Adding OSA in cement production increased the sample's compressive strength • When the OSA particle size is smaller than the clinker, the cement grinding process is faster and requires less energy https://doi.org/10.1007/s44290-024-00027-5…”
Section: Reviewmentioning
confidence: 99%
“…Jordan has long been known for its rich mineral resources, and the mining industry has played an important role in the country's economy. Phosphate, limestone, copper, and oil shale are the important minerals extracted in Jordan, and they are economically significant [18]- [21]. Due to its abundant phosphate reserves, Jordan has played a crucial role in the worldwide phosphate industry.…”
Section: Introductionmentioning
confidence: 99%
“…The nation is renowned for its abun-dant reserves of superior-grade limestone, which finds extensive application in several sectors. Limestone is an essential primary material in industries such as construction, cement and lime production [18], [20]. The limestone mined in Jordan is often distinguished by its advantageous chemical composition, rendering it appropriate for many industrial purposes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Important problem is to use more "Green" concrete using fiber-reinforced concrete with oil shale ash as a cement partial replacement in material [7] [8]. Oil shale ash is a by-product of the mining, processing, and burning of oil shale that is produced during the energy generation process in Estonia [9] [10] [11].…”
Section: Introductionmentioning
confidence: 99%